2001
DOI: 10.1055/s-2001-18355
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds with Anti-Inflammatory Activity fromEupatorium buniifolium

Abstract: Anti-inflammatory activity was detected in the CH(2)Cl(2) extract of the aerial parts of Eupatorium buniifolium using the TPA-mouse ear model. Three compounds isolated from this extract, by bioassay-guided fractionation, significantly inhibited the inflammatory response. The compounds were identified as 5,7,5'-trihydroxy-3,6,2',4'-tetramethoxyflavone (1), scopoletin (2) and centaureidin (3) which inhibited the edema by 67.3 %, 59.8 % and 49.7 %, respectively, at a dose of 1 mg/ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…So far more than 1300 types of coumarin have been identified as natural or synthesized compounds. Coumarins have recently been reported to have interesting pharmacologic and biochemical properties such as antioxidative, 1,2) antiinflammatory, and antiallergic effects, 3,4) inhibition of platelet aggregation 5) and protein kinase, 6) induction of apoptosis, 7) and antiviral, 8) antidifferentiative, 9) and antimutagenic activity. 10) Melanin pigment is a heteropolymer of indole compounds synthesized within melanocytes in the epidermis.…”
mentioning
confidence: 99%
“…So far more than 1300 types of coumarin have been identified as natural or synthesized compounds. Coumarins have recently been reported to have interesting pharmacologic and biochemical properties such as antioxidative, 1,2) antiinflammatory, and antiallergic effects, 3,4) inhibition of platelet aggregation 5) and protein kinase, 6) induction of apoptosis, 7) and antiviral, 8) antidifferentiative, 9) and antimutagenic activity. 10) Melanin pigment is a heteropolymer of indole compounds synthesized within melanocytes in the epidermis.…”
mentioning
confidence: 99%
“…Ursolic acid was also reported to suppress the expression of proinflammatory enzymes, cyclooxygenase-2 and inducible nitric oxide synthase (Suh et al, 1998), and to inhibit nuclear factor-κB activation (Shishodia et al, 2003). Scopoletin was found to inhibit 12-Otetradecanoylphorbol 13-acetate-induced mouse ear oedema (Muschietti et al, 2001), and to suppress the expression of inducible nitric oxide synthase from lipopolysaccharide-induced macrophages . These findings strongly suggest that ursolic acid and scopoletin may contribute, at least in part, to the antiinflammatory activity exerted by S. deltoides.…”
Section: Figurementioning
confidence: 99%
“…A variety of bioactivities have been ascribed to this compound, including antiinflammatory, antioxidation, antitumor, and anti-angiogenesis activities. These activities are potentially due to inhibition of nitric oxide synthesis, COX-2 expression, pro-inflammatory cytokine production, and endothelial cell migration and tube formation [Muschietti et al, 2001;Ng et al, 2003;Manuele et al, 2006;Ding et al, 2005;Pan et al, 2009]. Recently, we found that intraperitoneal injection of scopoletin effectively reduced the inflammation of joints and synovial thickening in AA rats.…”
Section: Introductionmentioning
confidence: 96%